How Universal is Chomskys Universal Grammar? - Achmad Effendi Kadarisman (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
The publication of this book signifies three important things. First, syntactic theory in generative grammarÃ¢â¬âafter nearly five decades of its inceptionÃ¢â¬âremains a thriving discipline. In fact, it seems to have been too progressive and dynamic, making some drastic change in a rather unexÃÂpected manner. Considering the proliferation and world-wide fame of the Government-Binding (GB) Theory during the 1980s and early 1990s, Chomsky s publication of The Minimalist Program (1995) might have taken GB syntacticians by surprise, since this book was intended as a major reviÃÂsion of GB syntax. Second, syntax, as ever, remains central and plays the leading role in generative grammar. The creative aspect of human lanÃÂguage, the argument goes, is best explained by syntaxÃ¢â¬âpart of the linguisÃÂtic competence which contributes most to accounting for native speakers ability to understand and produce novel utterances in their language. The centrality of syntax also shows up very clearly in the most influential books by Chomsky. Prior to The Minimalist Program, the earlier hallmarks in the generative enterprise are Syntactic Structures (1957), Aspects of the Theory of Syntax (1965), and Lectures on Government and Binding (1981). These books, while dealing with linguistic theory in general, dwelled heavily into syntax. Third, as is "notorious" among students of language, Chomsky re-mains a hard reading. Readers familiar with GB Theory would recall that Chomsky 1981 is intellectually accessible only to well-trained syntacticians. Therefore, during the past two decades syntacticians were busy "translatÃÂing" GB syntax to make it accessible to language students in general. Works by Cook (1988), Cowper (1992), Radford (1988), and Sells (1985)Ã¢â¬âto cite just a few examplesÃ¢â¬âare simplified versions of GB syntax intended for beginners. It is along this line of "simplification" that the book now being reviewed was written. In other words, the original version of the Minimalist Program, like that of GB Theory, might be way beyond beginning students of linguistics.